A New Standard for Information Organization: Resource Description and Access (RDA) - Özel, Nevzat (Information World, 2015)
The new cataloguing standard RDA, that replace Anglo-American Cataloging Rules 2 (AACR2) has been designed to organize information resources and provide access to these resources. It aims to simplify the use and interpretation of cataloging rules, have an effective bibliographic control over all information environment, to form a hierarchical and logical relationship among information resources, integrate the library data to the data from different sources, and introduce a functional structure to access information resources. Towards these aims, RDA intends to rearrange bibliographic universe in a more effective way. In this study, the new approaches, structure, terminology, rules, applications and elements relation with RDA implementation have been explained based on literature. In addition, RDA studies and initiatives around the world and in Turkey have been addressed.
Keywords: Cataloguing; Information organization; Bibliographic control; Resource Description and Access